Structural analysis of two different stent configurations. Issue 8 (11th June 2017) - Simão, M.; Ferreira, J. M.; Mora-Rodriguez, J.; Ramos, H. M.
Abstract: Two different stent configurations (i.e. the well known Palmaz–Schatz (PS) and a new stent configuration) are mechanically investigated. A finite element model was used to study the two geometries under combining loads and a computational fluid dynamic model based on fluid structure interaction was developed investigating the plaque and the artery wall reactions in a stented arterial segment. These models determine the stress and displacement fields of the two stents under internal pressure conditions. Results suggested that stent designs cause alterations in vascular anatomy that adversely affect arterial stress distributions within the wall, which have impact in the vessel responses such as the restenosis. The hemodynamic analysis shows the use of new stent geometry suggests better biofluid mechanical response such as the deformation and the progressive amount of plaque growth.